Towards sustainable informal settlements: a toolkit for community-led upgrading in Durban. Issue 2 (16th October 2020) - Georgiadou, Maria Christina; Loggia, Claudia; Bisaga, Iwona; Parikh, Priti
Abstract : Across sub-Saharan Africa, 238 million people live in slums or informal settlements. Because of rapid urbanisation and population growth, informal settlements have become a major challenge in the urban landscape, exacerbating issues related to poverty, inadequate infrastructure, housing and poor living conditions. As part of a collaborative interdisciplinary project ISULABANTU, this paper provides an overview of toolkits focused on informal settlement upgrading (ISU) in South Africa and presents the process of an integrated toolkit development for sustainable human settlements in Durban, which was informed by participatory action research and co-production strategies. A toolkit can be a valuable and effective way of engaging communities in the process of ISU and for community members to take full ownership of the process, designing strategies that best respond to their needs. The review of existing toolkits has revealed several critical gaps related to community-led practices, integrated approaches to housing and environmental management, and gender. The integrated ISULABANTU toolkit aims to fill these gaps and complement the existing resources. It provides a framework for action research, active involvement of and partnership building with local communities in upgrading practices required to achieve sustainable human settlements.